Projection of R&D intensive enterprise growth to the year 2020: Implications for EU policy? - Peter Voigt; Pietro Moncada-Paternò-Castello (European Commission, Joint Research Centre (JRC), 2012)
The paper investigates how sector composition and the magnitude of R&D investment in the EU may differ in 2020 in comparison to the past, if a selection of top R&D-investing SMEs were assumed to be on a fast growth track while the top R&D-investing large-scale companies continue to grow as before. The background of this research objective is the emerging focus on SMEs – and in particular the fast-growing among them – with regard to the "Europe 2020" policy strategy. The study relies on the sample of top R&D-investing firms as given by the latest available "EU Industrial R&D Investment Scoreboard" editions, building there from an unbalanced panel. Scenarios were developed by distinguishing SMEs' assumed growth paths vs. that of large scale companies. A linear prediction model has been used to calculate the scenario simulations. Overall, the study indicates that if one expects the (R&D-intensive) small firms to be a driving force for a substantial structural change in the EU economy, from being driven by medium-tech sectors towards a high-tech based economy, it requires either a significant longer-term horizon of the assumed fast growth track than the simulated 10 years, or small firms' growth figures which even exceed the assumed annual 30% (as in the most optimistic scenario). Neither case appears to be particularly realistic. Hence, we need more top R&D investors in Europe to further intensify their engagement in R&D (increasing volume and R&D intensity) as well as numerous small firms that start and/or significantly increase their existing R&D activities and thus seek to become large firms and (global) leading R&D investors. Accordingly, a broad R&D and innovation (policy) strategy is needed with policy interventions which also target well all these options; i.e. stimulating firm growth and R&D and innovation-intensity across firm-sized classes.
Keywords: O31; L11; L25; R38; 330; SME; company growth; industrial dynamics; structural change; R&D/ innovation policy; Barcelona target; Europe 2020